Incessant conceptual/industrial transformation of automobiles - Fumio Kodama (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
In order to comprehend the prospect of a future automobile industry, the development path of the automobile industry is reviewed. It is found that the industry has experienced an incessant conceptual transformation, dominant design, emission control, fuel efficiency, product integrity, modularization, and hybridization. An industrial transformation is also identified, comprised of inter-firm competition, inter-industry competition, and inter-industry collaboration. It is concluded that in the coming age of self-driving, global partnering including IT companies will forge a new path for industrial development. Additionally, the pattern of innovation will involve business model creation rather than simple product/process innovations, such as the PC industry experienced after its stand-alone innovation had been accomplished.
Keywords: 650; Dominant design; Hybrid car; Industrial transformation; Modularization; Product integrity; Self-driving